Transnationalization of Public Spheres - Weßler, H. author. aut Link
XIV, 269 p.
Keywords: This book takes a fresh look at a widely debated question in international relations and political communication research: How can public discourses contribute to democratic governance beyond the nation state? The book combines quantitative and qualitative analyses of media content and evaluates them from a democratic theory perspective.